Impact of prenatal and postnatal nutrition on pain modulation and stress response in offspring - Cernigliaro, Federica; Raieli, Vincenzo; Correnti, Edvige; Santangelo, Giuseppe; Nardello, Rosaria (Frontiers in Nutrition, 2025)
Nutrition is an environmental risk factor playing a pivotal role in predisposing to various diseases. Especially prenatal nutrition induces adaptation processes, known as early programming, leading to the alteration of fetal growth and brain development. Our previous study focused on the relation between prenatal nutritional factors and neurodevelopmental disorders. This narrative review analyses instead how prenatal and postnatal nutrition may impact many other pathways, for example, pain modulation and stress response. The alteration of these pathways is mediated by modification of the activity of the HPA (hypothalamic–pituitary–adrenal) axis, dysregulation of the gut-brain axis, and epigenetic changes induced by food. Diet and alterations in levels of macronutrients or micronutrients can alter the gene expression both in the uterus and early stage of life, increasing the susceptibility to many pathologies, related to metabolic alteration, but also cognitive impairment. Moreover, maternal diet can influence brain excitability and neuropeptides, and the release of neurotransmitters. We searched keywords such as “prenatal nutrition and pain modulation” on PubMed and Google Scholar, selecting the main reviews and excluding individual cases. Unfortunately, few data investigated this topic, so future perspectives may include more studies regarding the pathophysiology of these alterations, in order to understand how to improve and promote offspring’s health, through maternal and early nutrition.